Coating for preventing iodine contrast agent from crystallizing and preparation method thereof
By introducing low surface energy fluorine elements, hydroxyl acrylic resin, isophorone diisocyanate, and synergists into the coating to form a three-dimensional network structure, the problems of iodine contrast agent crystallization and adhesion are solved, enabling continuous long-term cleaning and inspection of equipment.
Patent Information
- Application Number
- CN202511474277.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-15
- Publication Date
- 2026-01-06
AI Technical Summary
Existing technologies cannot effectively prevent iodine contrast agents from crystallizing and adhering in medical imaging equipment, leading to problems such as connector adhesion and difficulty in cleaning the equipment casing.
A coating that prevents iodine contrast agent crystallization is employed. By introducing low surface energy fluorine into the coating, a three-dimensional network structure is formed using hydroxyl acrylic resin, isophorone diisocyanate, and synergists such as carboxylated graphene-iron fluoride composite particles. This reduces the surface free energy of the coating, improves its water resistance, and prevents iodine contrast agent crystallization and adhesion.
It effectively prevents the crystallization and adhesion of iodine contrast agents on the equipment casing and pipeline joints, avoiding joint adhesion and difficulty in cleaning the equipment casing caused by iodine contrast agent coagulation, thus ensuring the continuity and safety of medical imaging examinations.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of medical device technology, and in particular to a coating for preventing the crystallization of iodine contrast agents and its preparation method. Background Technology
[0002] Iodine contrast agents are iodine-containing substances primarily used in medical imaging examinations to enhance the visibility of specific structures or abnormalities within the body. Based on their chemical structure and permeability, they can be classified into ionic and non-ionic types. Ionic iodine contrast agents have higher permeability and are often used in examinations requiring high contrast, such as angiography; while non-ionic iodine contrast agents have lower permeability and are suitable for patients with impaired liver or kidney function, such as those undergoing CT scans.
[0003] When iodine contrast agents are used at high concentrations or for extended periods, they are prone to solidification upon contact with air, leading to crystallization or precipitation. This is especially true at joints or on exposed surfaces, where crystallization or deposition can cause pipe blockage. To improve the utilization rate of iodine contrast agents, existing technologies employ fluorinated coatings on the inner walls of pipes or equipment. This effectively reduces crystallization and adhesion, extending pipe uptime and minimizing interruptions or operational failures due to blockages. This approach is particularly suitable for scenarios requiring long-term or repeated use of contrast agents, such as high-concentration iodine contrast agents.
[0004] CN113694215A discloses a composition of magnetic nanodroplets, a magnetic contrast agent, and a method for preparing the same. The composition contains modified magnetic nanoparticles coated with silica and modified with fluorosilane. The contrast agent exhibits excellent magnetic responsiveness and in vivo stability, reduces immune capture, and can achieve tumor-targeted imaging and local drug delivery under the synergy of an external magnetic field and ultrasound, providing a novel carrier for precision diagnosis and treatment.
[0005] CN105377244A discloses a solid nanoparticle with an inorganic coating. This invention addresses the problems of easy aggregation, low bioavailability of poorly soluble drugs, and insufficient targeting of existing nanoparticles by proposing an innovative solution: the nanoparticle is composed of a solid core containing bioactive substances such as alprazolam and paclitaxel and an inorganic coating that encapsulates the core. An intermediate layer containing surfactants can be provided between the core and the coating. The outer surface of the coating can be connected to targeting molecules such as antibodies and nucleic acids through silane functional groups.
[0006] The solutions reported in these patent documents cannot simultaneously solve the problems of crystallization and adhesion faced by iodine contrast agents in practical applications. Summary of the Invention
[0007] In view of the above-mentioned deficiencies of the prior art, the technical problem to be solved by the present invention is to provide a coating that prevents the crystallization of iodine contrast agent. When applied to the surface of medical imaging examination equipment, such as the outer shell, inner wall of pipeline, and pipeline joints, the coating can reduce the surface free energy, improve the water resistance of the coating, and prevent the crystallization and adhesion of iodine contrast agent. This avoids the problems of joint adhesion and difficulty in cleaning the equipment shell caused by contrast agent coagulation under long-term use.
[0008] To achieve the above objectives, the present invention provides a coating for preventing the crystallization of iodine contrast agents and a method for preparing the same.
[0009] The method for preparing the coating that prevents iodine contrast agent crystallization is as follows: The coating that prevents iodine contrast agent crystallization is sprayed onto the application surface and cured at 70-80°C for 1-3 hours to obtain the coating that prevents iodine contrast agent crystallization.
[0010] The application surface is one of the following: equipment casing, pipeline inner wall, and pipeline joint.
[0011] The coating thickness is 5-15 μg / mm. 2 .
[0012] The preparation method of the coating for preventing crystallization of iodine contrast agent is as follows, in parts by weight: Disperse 1-15 parts of hydroxyl acrylic resin and 0.5-1.5 parts of synergist into 6-10 parts of mixed solution, and ultrasonically disperse for 20-40 minutes; add 0.04-0.06 parts of defoamer and 0.04-0.06 parts of dispersant and continue stirring for 0.5-1 hour; add 4-6 parts of curing agent and continue stirring for 0.5-1 hour, and disperse and grind until the coating fineness is less than 80 μm to obtain the coating for preventing iodine contrast agent crystallization.
[0013] The mixed solution is a mixture of ethyl acetate and propylene glycol methyl ether acetate.
[0014] The curing agent is isophorone diisocyanate.
[0015] The synergist is one of carboxylated graphene, carboxylated graphene-iron fluoride composite particles, and modified carboxylated graphene-iron fluoride composite particles. More preferably, the synergist is modified carboxylated graphene-iron fluoride composite particles.
[0016] The preparation method of the modified carboxyl-graphene-iron fluoride composite particles is as follows, in parts by weight: M1. Add 0.5-1.5 parts of carboxylated graphene to 10-20 parts of polyethylene glycol, and ultrasonically disperse for 0.5-1 hours to obtain a dispersion. Add hydrofluoric acid aqueous solution and stir at room temperature for 1-2 hours. Add 8-12 parts of ferric trifluoromethanesulfonate aqueous solution and stir for 1-3 hours. Stir at 110-130°C for 1-2 hours. After cooling to room temperature, centrifuge 2-4 times, collect the precipitate, wash 2-4 times with anhydrous ethanol, and dry to obtain carboxylated graphene-ferric fluoride composite particles. M2. Add 0.05-0.15 parts of 1H,1H,2H,2H-perfluorooctyltriethoxysilane to 20-30 parts of anhydrous ethanol and stir for 0.5-1 hour. Add 0.5-1.5 parts of carboxylated graphene-iron fluoride composite particles and stir for 1-2 hours. After drying, the modified carboxylated graphene-iron fluoride composite particles are obtained. Alternatively, add 0.05-0.15 parts of 1H,1H,2H,2H-perfluorooctyltriethoxysilane and 0.02-0.04 parts of phosphazene compound to 20-30 parts of anhydrous ethanol and stir for 0.5-1 hour. Then add 0.5-1.5 parts of carboxylated graphene-iron fluoride composite particles and stir for 1-2 hours. After drying, the modified carboxylated graphene-iron fluoride composite particles are obtained.
[0017] The phosphazene compound is at least one of hexaphenoxycyclotriphosphazene, hexa(p-aminophenoxy)cyclotriphosphazene, and hexa(4-carboxyphenoxy)cyclotriphosphazene.
[0018] The hydrofluoric acid aqueous solution is a 25-35 wt% hydrofluoric acid aqueous solution.
[0019] The ferric trifluoromethanesulfonate aqueous solution is a 5-15 wt% ferric trifluoromethanesulfonate aqueous solution.
[0020] The technical problem to be solved by the coating for preventing the crystallization of iodine contrast agent of the present invention is to provide a coating that prevents the crystallization of iodine contrast agent. When applied to the surface of medical imaging examination equipment, such as the outer shell, inner wall of pipeline, and pipeline joints, the coating can reduce the surface free energy, improve the water resistance of the coating, and prevent the crystallization and adhesion of iodine contrast agent. This avoids the problems of joint adhesion and difficulty in cleaning the equipment shell caused by contrast agent coagulation under long-term use.
[0021] To achieve the above objectives, this invention uses polyurethane as the coating matrix, which plays a key role in adhesion and prevents the coating from peeling off due to water flow impact or contrast agent erosion during long-term use. Isophorone diisocyanate curing agent is added to crosslink with hydroxyl acrylic resin, forming a three-dimensional network structure, improving the coating's density and resistance to deformation, and reducing the penetration channels of water molecules and iodine contrast agent molecules. This invention also incorporates a synergist, which is one of carboxylated graphene, carboxylated graphene-iron fluoride composite particles, or modified carboxylated graphene-iron fluoride composite particles. The carboxylated graphene utilizes its sheet-like nanostructure to construct a micro-rough surface in the coating, providing support for subsequent loading of low surface energy components and enhancing the coating's adhesion. Further composite modification with ferric trifluoromethanesulfonate is added. When the carboxyl and hydroxyl groups on the surface of the carboxylated graphene interact with ferric trifluoromethanesulfonate, they form stable coordination bonds with iron ions through lone pair electrons, weakening the graphene... Van der Waals forces between the layers ensure uniform dispersion of carboxylated graphene in the coating. Polyethylene glycol acts as a solvent to ensure uniform contact of the reactants in the system. Hydrofluoric acid forms more active sites on the surface of carboxylated graphene through weak etching, enhancing its binding ability and loading conditions with subsequent iron and fluoride ions. The iron ions from ferric trifluoromethanesulfonate can coordinate with the polar groups on the surface of carboxylated graphene, while the fluoride ions react with the iron ions to form iron fluoride during the reaction process. At the same time, low surface energy fluorine is introduced, ultimately preparing carboxylated graphene-iron fluoride composite particles.
[0022] This invention also introduces 1H,1H,2H,2H-perfluorooctyltriethoxysilane to hydrophobically modify carboxylated graphene-iron fluoride composite particles. By improving the hydrophobicity of the coating, and through the chemical bonding between the silane group in the silane molecule and the hydroxyl and carboxyl groups on the surface of the composite particles, the low surface energy groups of 1H,1H,2H,2H-perfluorooctyl are uniformly covered on the surface of the composite particles, achieving a uniform distribution of low surface energy components in the coating. At the same time, it improves the overall density of the coating and reduces the damage to the coating structure and the impact on service life caused by iodine contrast agents in practical applications. Furthermore, this invention incorporates a phosphazene compound and 1H,1H,2H,2H-perfluorooctyltriethoxysilane for composite modification. The phosphazene compound is at least one of hexaphenoxycyclotriphosphazene, hexa(p-aminophenoxy)cyclotriphosphazene, and hexa(4-carboxyphenoxy)cyclotriphosphazene. Specifically, hexa(4-carboxyphenoxy)cyclotriphosphazene forms hydrogen bonds with the carboxyl group of the graphene through the para-carboxyl group of the benzene ring, and undergoes a condensation reaction with the silane silanol group. This dual-site chemical bonding creates pores in the coating. Further reduction in porosity and surface free energy results in optimal anti-crystallization performance. Hexa(p-aminophenoxy)cyclotriphosphazene improves anti-crystallization and water resistance by bonding the para-amino group of the benzene ring to the carboxyl group on the graphene surface. However, the amino group is susceptible to inactivation by residual components, thus its effect is slightly inferior to the carboxyl type. Hexaphenoxycyclotriphosphazene lacks polar active functional groups and only achieves physical adsorption through π-π stacking of the benzene ring and graphene. The coating does not show significant densification improvement, resulting in limited improvement in anti-crystallization and water resistance. It is particularly suitable for repeated injections of high-concentration iodine contrast agents, especially in the application of Maiwei's 24-hour products. It can maintain the cleanliness of the equipment casing, pipeline inner walls, and pipeline joints for extended periods, preventing examination interruptions caused by iodine contrast agent crystallization and ensuring the continuity and safety of medical imaging examinations.
[0023] The beneficial effects of this invention are: Compared with existing technologies, the coating for preventing iodine contrast agent crystallization of the present invention incorporates a synergist during its preparation. This synergist is one of carboxylated graphene, carboxylated graphene-iron fluoride composite particles, or modified carboxylated graphene-iron fluoride composite particles. By introducing low surface energy fluorine elements into the coating, the damage to the coating structure and its impact on service life caused by iodine contrast agent in practical applications are reduced. This avoids problems such as joint adhesion and difficulty in cleaning the equipment casing due to contrast agent coagulation under long-term use. It is particularly suitable for scenarios involving repeated injection of high-concentration iodine contrast agents, especially in the application of Maiwei 24-hour products. It can maintain the cleanliness of the equipment casing, pipeline inner walls, and pipeline joints for a long time, avoiding examination interruptions caused by iodine contrast agent crystallization blockage, and ensuring the continuity and safety of medical imaging examinations. Detailed Implementation
[0024] The parameters of the specific chemical substances used in the examples are from the following sources: Hydroxy acrylic resin: The hydroxyl content in the solid is 1.3wt%, the maximum water content is 0.1wt%, the brand is HELIOSRESINS, and the model is DOMACRYL 5196 60 SA.
[0025] Carboxylated graphene: diameter 0.5-3μm, thickness 0.55-3.74nm, number of layers ≤10, sourced from Beijing Bailingwei Technology Co., Ltd., product number 926928.
[0026] Ferric trifluoromethanesulfonate: CAS number is 63295-48-7; 1H,1H,2H,2H-Perfluorooctyltriethoxysilane: CAS No. 51851-37-7.
[0027] Comparative Example 1 A method for preparing a coating that prevents crystallization of iodine contrast agents is as follows: 12g of hydroxyl acrylic resin was dispersed in a mixed solution of 6g ethyl acetate and 2g propylene glycol methyl ether acetate and ultrasonically dispersed for 30 minutes; 0.05g of defoamer BYK-141 and 0.05g of dispersant BYK-163 were added and stirring was continued for 0.5 hours; 5g of isophorone diisocyanate was added and stirring was continued for 0.5 hours, and the mixture was dispersed and ground until the fineness of the coating was less than 80μm to obtain the coating for preventing the crystallization of iodine contrast agent.
[0028] Example 1 A method for preparing a coating that prevents crystallization of iodine contrast agents is as follows: 12g of hydroxyl acrylic resin and 1g of carboxylated graphene were dispersed in a mixed solution of 6g ethyl acetate and 2g propylene glycol methyl ether acetate and ultrasonically dispersed for 30 minutes. 0.05g of defoamer BYK-141 and 0.05g of dispersant BYK-163 were added and stirring was continued for 0.5 hours. 5g of isophorone diisocyanate was added and stirring was continued for 0.5 hours. The mixture was then dispersed and ground until the coating fineness was less than 80μm to obtain the coating for preventing the crystallization of iodine contrast agent.
[0029] Example 2 A method for preparing a coating that prevents crystallization of iodine contrast agents is as follows: 12g of hydroxyl acrylic resin, 0.5g of carboxylated graphene, and 0.5g of ferric trifluoromethanesulfonate were dispersed in a mixed solution of 6g of ethyl acetate and 2g of propylene glycol methyl ether acetate, and ultrasonically dispersed for 30 minutes. 0.05g of defoamer BYK-141 and 0.05g of dispersant BYK-163 were added, and stirring was continued for 0.5 hours. 5g of isophorone diisocyanate was added, and stirring was continued for 0.5 hours. The mixture was then dispersed and ground until the coating fineness was less than 80μm to obtain the coating for preventing iodine contrast agent crystallization.
[0030] Example 3 A method for preparing a coating that prevents crystallization of iodine contrast agents is as follows: 12g of hydroxyl acrylic resin and 1g of carboxylated graphene-ferric fluoride composite particles were dispersed in a mixed solution of 6g ethyl acetate and 2g propylene glycol methyl ether acetate and ultrasonically dispersed for 30 minutes. 0.05g of defoamer BYK-141 and 0.05g of dispersant BYK-163 were added and stirring was continued for 0.5 hours. 5g of isophorone diisocyanate was added and stirring was continued for 0.5 hours. The mixture was then dispersed and ground until the coating fineness was less than 80μm to obtain the coating for preventing iodine contrast agent crystallization.
[0031] The preparation method of the carboxyl-graphene-iron fluoride composite particles is as follows: 0.1g of carboxylated graphene was added to 15g of polyethylene glycol 400 and ultrasonically dispersed for 0.5 hours to obtain a dispersion. 1g of 30wt% hydrofluoric acid aqueous solution was added and stirred at room temperature for 1.5 hours. 10g of 10wt% ferric trifluoromethanesulfonate aqueous solution was added and stirred for 2 hours. The mixture was stirred at 120°C for 1.5 hours. After cooling to room temperature, the mixture was centrifuged three times at 15000rpm. The precipitate was collected, washed three times with anhydrous ethanol, and dried to obtain carboxylated graphene-ferric fluoride composite particles.
[0032] Example 4 A method for preparing a coating that prevents crystallization of iodine contrast agents is as follows: 12g of hydroxyl acrylic resin and 1g of modified carboxylated graphene-iron fluoride composite particles were dispersed in a mixed solution of 6g ethyl acetate and 2g propylene glycol methyl ether acetate and ultrasonically dispersed for 30 minutes. 0.05g of defoamer BYK-141 and 0.05g of dispersant BYK-163 were added and stirring was continued for 0.5 hours. 5g of isophorone diisocyanate was added and stirring was continued for 0.5 hours. The mixture was then dispersed and ground until the coating fineness was less than 80μm to obtain the coating for preventing iodine contrast agent crystallization.
[0033] The preparation method of the modified carboxyl-graphene-iron fluoride composite particles is as follows: M1. Add 0.1g of carboxylated graphene to 15g of polyethylene glycol 400 and ultrasonically disperse for 0.5 hours to obtain a dispersion. Add 1g of 30wt% hydrofluoric acid aqueous solution and stir at room temperature for 1.5 hours. Add 10g of 10wt% ferric trifluoromethanesulfonate aqueous solution and stir for 2 hours. Stir at 120°C for 1.5 hours. After cooling to room temperature, centrifuge at 15000rpm 3 times, collect the precipitate, wash 3 times with anhydrous ethanol, and dry to obtain carboxylated graphene-ferric fluoride composite particles. M2. Add 0.1g of 1H,1H,2H,2H-perfluorooctyltriethoxysilane to 2.5g of anhydrous ethanol and stir for 0.5 hours. Add 1g of carboxylated graphene-iron fluoride composite particles and stir for 1.5 hours. After drying, the modified carboxylated graphene-iron fluoride composite particles are obtained.
[0034] Example 5 A method for preparing a coating that prevents crystallization of iodine contrast agents is as follows: 12g of hydroxyl acrylic resin and 1g of modified carboxylated graphene-iron fluoride composite particles were dispersed in a mixed solution of 6g ethyl acetate and 2g propylene glycol methyl ether acetate and ultrasonically dispersed for 30 minutes. 0.05g of defoamer BYK-141 and 0.05g of dispersant BYK-163 were added and stirring was continued for 0.5 hours. 5g of isophorone diisocyanate was added and stirring was continued for 0.5 hours. The mixture was then dispersed and ground until the coating fineness was less than 80μm to obtain the coating for preventing iodine contrast agent crystallization.
[0035] The preparation method of the modified carboxyl-graphene-iron fluoride composite particles is as follows: M1. Add 0.1g of carboxylated graphene to 15g of polyethylene glycol 400 and ultrasonically disperse for 0.5 hours to obtain a dispersion. Add 1g of 30wt% hydrofluoric acid aqueous solution and stir at room temperature for 1.5 hours. Add 10g of 10wt% ferric trifluoromethanesulfonate aqueous solution and stir for 2 hours. Stir at 120°C for 1.5 hours. After cooling to room temperature, centrifuge at 15000rpm 3 times, collect the precipitate, wash 3 times with anhydrous ethanol, and dry to obtain carboxylated graphene-ferric fluoride composite particles. M2. Add 0.07g of 1H,1H,2H,2H-perfluorooctyltriethoxysilane and 0.03g of hexaphenoxycyclotriphosphazene to 25g of anhydrous ethanol and stir for 0.5 hours. Add 1g of carboxylated graphene-iron fluoride composite particles and stir for 1.5 hours. After drying, the modified carboxylated graphene-iron fluoride composite particles are obtained.
[0036] Example 6 A method for preparing a coating that prevents crystallization of iodine contrast agents is as follows: 12g of hydroxyl acrylic resin and 1g of modified carboxylated graphene-iron fluoride composite particles were dispersed in a mixed solution of 6g ethyl acetate and 2g propylene glycol methyl ether acetate and ultrasonically dispersed for 30 minutes. 0.05g of defoamer BYK-141 and 0.05g of dispersant BYK-163 were added and stirring was continued for 0.5 hours. 5g of isophorone diisocyanate was added and stirring was continued for 0.5 hours. The mixture was then dispersed and ground until the coating fineness was less than 80μm to obtain the coating for preventing iodine contrast agent crystallization.
[0037] The preparation method of the modified carboxyl-graphene-iron fluoride composite particles is as follows: M1. Add 0.1g of carboxylated graphene to 15g of polyethylene glycol 400 and ultrasonically disperse for 0.5 hours to obtain a dispersion. Add 1g of 30wt% hydrofluoric acid aqueous solution and stir at room temperature for 1.5 hours. Add 10g of 10wt% ferric trifluoromethanesulfonate aqueous solution and stir for 2 hours. Stir at 120°C for 1.5 hours. After cooling to room temperature, centrifuge at 15000rpm 3 times, collect the precipitate, wash 3 times with anhydrous ethanol, and dry to obtain carboxylated graphene-ferric fluoride composite particles. M2. Add 0.07g of 1H,1H,2H,2H-perfluorooctyltriethoxysilane and 0.03g of hexa(p-aminophenoxy)cyclotriphosphazene to 25g of anhydrous ethanol and stir for 0.5 hours. Then add 1g of carboxylated graphene-iron fluoride composite particles and stir for 1.5 hours. After drying, the modified carboxylated graphene-iron fluoride composite particles are obtained.
[0038] Example 7 A method for preparing a coating that prevents crystallization of iodine contrast agents is as follows: 12g of hydroxyl acrylic resin and 1g of modified carboxylated graphene-iron fluoride composite particles were dispersed in a mixed solution of 6g ethyl acetate and 2g propylene glycol methyl ether acetate and ultrasonically dispersed for 30 minutes. 0.05g of defoamer BYK-141 and 0.05g of dispersant BYK-163 were added and stirring was continued for 0.5 hours. 5g of isophorone diisocyanate was added and stirring was continued for 0.5 hours. The mixture was then dispersed and ground until the coating fineness was less than 80μm to obtain the coating for preventing iodine contrast agent crystallization.
[0039] The preparation method of the modified carboxyl-graphene-iron fluoride composite particles is as follows: M1. Add 0.1g of carboxylated graphene to 15g of polyethylene glycol 400 and ultrasonically disperse for 0.5 hours to obtain a dispersion. Add 1g of 30wt% hydrofluoric acid aqueous solution and stir at room temperature for 1.5 hours. Add 10g of 10wt% ferric trifluoromethanesulfonate aqueous solution and stir for 2 hours. Stir at 120°C for 1.5 hours. After cooling to room temperature, centrifuge at 15000rpm 3 times, collect the precipitate, wash 3 times with anhydrous ethanol, and dry to obtain carboxylated graphene-ferric fluoride composite particles. M2, 0.07g of 1H,1H,2H,2H-perfluorooctyltriethoxysilane, and 0.03g of hexa(4-carboxyphenoxy)cyclotriphosphazene were added to 25g of anhydrous ethanol and stirred for 0.5 hours. Then, 1g of carboxylated graphene-iron fluoride composite particles were added and stirred for 1.5 hours. After drying, modified carboxylated graphene-iron fluoride composite particles were obtained.
[0040] Test Example 1 The coatings for preventing iodine contrast agent crystallization obtained by the preparation methods of Comparative Example 1 and Examples 1-7 were respectively coated onto glass slides with dimensions of 25.4 mm × 76.2 mm × 1 mm and cured at 75°C for 2 hours to obtain the coating samples for preventing iodine contrast agent crystallization, with a coating thickness of 10 μg / mm. 2 Five sets of samples were prepared for each example. The contact angles of the coating samples of Comparative Example 1 and Examples 1-7 with water and diiodomethane were measured using a JC2000C contact angle meter. The droplet size of the test liquid was 3 μL. The image was stopped and saved immediately after the droplet contacted the sample coating for 3 seconds, and the liquid contact angle was measured and calculated. The surface free energy of the coating samples of Comparative Example 1 and Examples 1-7 was calculated and recorded. The average value of the data was taken and summarized as shown in Table 1.
[0041] The formula for calculating surface energy is as follows: σ p s =[(137.5+256.1×cosθ H2O -118.6×cosθ CH2I2 ) / 44.92] 2 ; σ d s =[(139.9+181.4×cosθ CH2I2 -41.5×cosθ H2O ) / 44.92] 2 ; σ s =σ p s +σ d s ; In the formula: θ H2O Water contact angle; θ CH2I2 : Diiodomethane contact angle; σ p s : Polar force; σ d s Dispersion force; σ s Surface free energy.
[0042] Table 1
[0043] The coating formulation of Comparative Example 1, with the addition of an synergist, exhibits high surface energy. The coating formulation of Example 1, containing carboxylated graphene, while capable of creating a certain surface roughness in polyurethane through its sheet-like structure, lacks low-surface-energy functional groups such as hydroxyl and carboxyl groups. Consequently, it cannot effectively reduce the interaction between the coating surface and polar substances like water, diiodomethane test liquid, and iodine contrast agents. Example 2 involves a simple mixture of carboxylated graphene and ferric trifluoromethanesulfonate. Although ferric trifluoromethanesulfonate contains fluorine, which can introduce low-surface-energy sites to some extent, and its ionic properties can weakly interact with the polar groups on the carboxylated graphene surface, the two do not form a stable composite structure. The fluorine is unevenly distributed on the coating surface, making it difficult to form a continuous and dense low-surface-energy layer. In the surface energy region, the reduction in surface free energy is low. In Example 3, the prepared carboxylated graphene-iron fluoride composite particles were added. Through the composite process, iron fluoride was uniformly loaded on the surface of carboxylated graphene, forming a denser low surface energy region. At the same time, the synergistic effect of the composite particles further optimized the microstructure of the coating surface and reduced the surface free energy. In Example 4, 1H,1H,2H,2H-perfluorooctyltriethoxysilane was introduced to modify the carboxylated graphene-iron fluoride composite particles. The perfluorooctyl group in this silane molecule has extremely low surface energy, and the silane group can chemically bond with the hydroxyl and carboxyl groups on the surface of the composite particles, so that the perfluoro groups are stably and uniformly covered on the coating surface, greatly increasing the density of low surface energy groups, while further improving the hydrophobicity of the coating surface and optimizing the microstructure. Examples 5-7, based on Example 4, respectively added hexaphenoxycyclotriphosphazene, hexa(p-aminophenoxy)cyclotriphosphazene, and hexa(4-carboxyphenoxy)cyclotriphosphazene to 1H,1H,2H,2H-perfluorooctyltriethoxysilane for composite modification. In Example 5, the hexaphenoxycyclotriphosphazene added had no polar active functional groups and only achieved dispersion through physical adsorption. While it slightly improved the hydrophobicity of the coating, it could not enhance the effect of low surface energy groups. In Example 6, the hexa(p-aminophenoxy)cyclotriphosphazene could form bonds through amino groups, assisting in the uniform distribution of perfluorinated groups, and its effect on reducing surface free energy was better than that of Example 5. However, the amino groups were susceptible to deactivation due to residual components. In Example 7, the hexa(4-carboxyphenoxy)cyclotriphosphazene formed a dense coating structure through carboxyl group bonding, enhancing the stability of low surface energy groups, maximizing the reduction of surface free energy, and achieving the best anti-crystallization effect. In the application of this invention, low surface energy groups can reduce the adhesion forces such as van der Waals forces and polar forces between the contrast agent molecules and the contrast agent molecules, thereby reducing the attachment sites of the contrast agent molecules and jointly achieving the effect of preventing the crystallization and adhesion of the iodine contrast agent. This effectively prevents the risk of crystallization and blockage caused by the adhesion of the iodine contrast agent to equipment shells, pipe joints, etc.
[0044] Test Example 2 The test was conducted according to the national standard GB / T 1733-1993 "Determination of Water Resistance of Paint Film". The coatings for preventing iodine contrast agent crystallization obtained by the preparation methods of Comparative Example 1 and Examples 1-7 were coated onto tinplate with dimensions of 120mm × 25mm × 0.2mm and cured at 75°C for 2 hours to obtain the coating samples for preventing iodine contrast agent crystallization. The coating thickness was 10μg / mm. 2 Three sets of samples were prepared for each embodiment.
[0045] Comparative Example 1 and Examples 1-7 samples were immersed in deionized water at room temperature, with 2 / 3 of the length of each sample plate submerged for 12 hours. After immersion, the samples were removed and placed in a room temperature environment. Bubbling and wrinkling were observed in the samples after the experiment, and recorded as +++, ++, and + according to the degree from high to low. The recovery time of the samples was observed without external force intervention. The shorter the recovery time, the better the water resistance of the sample plate. The average value of the data was taken and summarized as shown in Table 2.
[0046] Table 2 Bubbling phenomenon wrinkling Recovery time / h Comparative Example 1 +++ +++ 4.5 Example 1 ++ ++ 3.0 Example 2 ++ ++ 2.5 Example 3 ++ ++ 1.8 Example 4 ++ ++ 1.0 Example 5 ++ ++ 0.8 Example 6 ++ ++ 0.6 Example 7 + + 0.3 The coating samples of Comparative Example 1 and Examples 1-7 exhibited varying degrees of blistering and wrinkling during the 12-hour water resistance test. This was mainly due to differences in coating density, adhesion to the substrate, and water penetration resistance. Comparative Example 1, with the addition of an synergist, showed poor water resistance. Example 1, containing only carboxyl-based graphene, exhibited poor water resistance because its surface hydroxyl and carboxyl groups readily form hydrogen bonds with water molecules. Furthermore, the graphene sheet structure, when dispersed in the polyurethane matrix, easily forms micro-gaps, allowing water molecules to penetrate into the coating and substrate interface, thus damaging the coating adhesion. Prolonged immersion resulted in significant blistering and wrinkling. The recovery time was the longest, as water penetration required a considerable amount of time for evaporation and coating structure restoration. Example 2 introduced a simple physical mixture of ferric trifluoromethanesulfonate and carboxylated graphene. Although ferric trifluoromethanesulfonate could bind to the polar groups of carboxylated graphene through ionic interactions, slightly reducing polar sites and filling some gaps, the two did not form a stable composite structure. Uneven water molecule penetration channels still existed inside the coating, and blistering and wrinkling were not significantly improved, although they were improved compared to Example 1. Example 3 added the prepared carboxylated graphene-ferric fluoride composite particles. The composite process allowed the ferric fluoride to be uniformly loaded on the graphene surface. Through chemical bonding, the gaps inside the coating were reduced, and the fluorine element formed continuous hydrophobic regions, reducing the water molecule penetration rate, blistering, and wrinkling, and shortening the recovery time. Example 4 modifies the composite particles with 1H,1H,2H,2H-perfluorooctyltriethoxysilane. The silane group of the silane molecule forms a strong chemical bond with the surface group of the composite particles, which greatly improves the density of the coating. At the same time, the perfluorooctyl forms a high-density hydrophobic layer on the coating surface, which significantly inhibits the penetration of water molecules. Only slight bubbling and wrinkling occur, and the small amount of water that penetrates is easy to evaporate and has a short recovery time. Examples 5-7, based on Example 4, respectively added hexaphenoxycyclotriphosphazene, hexa(p-aminophenoxy)cyclotriphosphazene, and hexa(4-carboxyphenoxy)cyclotriphosphazene to 1H,1H,2H,2H-perfluorooctyltriethoxysilane for composite modification. Among them, the hexaphenoxycyclotriphosphazene in Example 5 only assisted in filling the coating gaps through physical adsorption, and had limited effect on improving the density. The hexa(p-aminophenoxy)cyclotriphosphazene in Example 6 can enhance the structural stability of the coating, reduce the water molecule penetration channels, and further shorten the recovery time. The hexa(4-carboxyphenoxy)cyclotriphosphazene in Example 7 can significantly improve the coating density and the integrity of the hydrophobic layer, with the least water molecule penetration, only slight blistering and wrinkling, the shortest recovery time, and the best water resistance.
[0047] The preferred embodiments of the present invention have been described in detail above. It should be understood that those skilled in the art can make numerous modifications and variations based on the concept of the present invention without creative effort. Therefore, all technical solutions that can be obtained by those skilled in the art based on the concept of the present invention through logical analysis, reasoning, or limited experimentation on the basis of existing technology should be within the scope of protection defined by the claims.
Claims
1. A method of making a coating to prevent crystallization of iodinated contrast agents, characterized by, The steps are as follows: A coating for preventing iodine contrast agent from crystallizing is sprayed to the application surface, and is cured at 70-80°C for 1-3 hours to obtain the coating for preventing iodine contrast agent from crystallizing; The preparation method of the coating for preventing iodine contrast agent from crystallizing is as follows: 1-15 parts of hydroxy acrylic resin and 0.5-1.5 parts of synergist are dispersed into 6-10 parts of mixed solution by weight, and are ultrasonically dispersed for 20-40 minutes; 0.04-0.06 parts of defoaming agent and 0.04-0.06 parts of dispersant are added, and stirring is continued for 0.5-1 hour; 4-6 parts of curing agent is added, and stirring is continued for 0.5-1 hour, and dispersion grinding is performed until the fineness of the coating is less than 80 μm to obtain the coating for preventing iodine contrast agent from crystallizing; The synergist is one of carboxylated graphene, carboxylated graphene-iron fluoride composite particles and modified carboxylated graphene-iron fluoride composite particles.
2. The method of claim 1, wherein the coating is prepared by the steps of: The application surface is one of equipment shell, pipeline inner wall and pipeline joint.
3. The method of claim 1, wherein the coating is prepared by the steps of: The coating thickness is 5-15 μg / mm 2 .
4. The method of claim 1, wherein the coating is prepared by the steps of: The mixed solution is a mixed solution of ethyl acetate and propylene glycol methyl ether acetate.
5. The method of claim 1, wherein the coating is prepared by the steps of: The synergist is modified carboxylated graphene-iron fluoride composite particles.
6. The method of claim 1 or 5, wherein the coating is prepared by the steps of: The preparation method of the modified carboxylated graphene-iron fluoride composite particles is as follows by weight: M1, 0.5-1.5 parts of carboxylated graphene is added into 10-20 parts of polyethylene glycol, and is ultrasonically dispersed for 0.5-1 hour to obtain a dispersion liquid, and 25-35 wt% hydrofluoric acid aqueous solution is added, and stirring is performed at room temperature for 1-2 hours, and 5-15 wt% iron triflate aqueous solution is added, and stirring is performed for 1-3 hours, and stirring is performed at 110-130°C for 1-2 hours, and after cooling to room temperature, centrifugation is performed for 2-4 times, and the precipitate is collected, and is washed with anhydrous ethanol for 2-4 times, and is dried to obtain carboxylated graphene-iron fluoride composite particles; M2, 0.05-0.15 parts of 1H, 1H, 2H, 2H-perfluorooctyl triethoxysilane is added into 20-30 parts of anhydrous ethanol, and stirring is performed for 0.5-1 hour, and 0.5-1.5 parts of carboxylated graphene-iron fluoride composite particles is added, and stirring is performed for 1-2 hours, and after drying, modified carboxylated graphene-iron fluoride composite particles are obtained; Or, 0.05-0.15 parts of 1H, 1H, 2H, 2H-perfluorooctyl triethoxysilane and 0.02-0.04 parts of phosphazene compound are added into 20-30 parts of anhydrous ethanol, and stirring is performed for 0.5-1 hour, and 0.5-1.5 parts of carboxylated graphene-iron fluoride composite particles is added, and stirring is performed for 1-2 hours, and after drying, modified carboxylated graphene-iron fluoride composite particles are obtained.
7. The method of claim 6, wherein the coating is prepared by the steps of: The phosphazene compound is at least one of hexaphenoxy cyclotriphosphazene, hexakis(p-aminophenoxy) cyclotriphosphazene and hexakis(4-carboxyphenoxy) cyclotriphosphazene.
8. The method of claim 6, wherein the coating is prepared by the steps of: The hydrofluoric acid aqueous solution is 25-35 wt% hydrofluoric acid aqueous solution.
9. The method of claim 6, wherein the coating is prepared by the steps of: The iron triflate aqueous solution is 5-15 wt% iron triflate aqueous solution.
10. A coating to prevent crystallization of iodinated contrast agents, characterized in that, The preparation method is prepared by any one of claims 1-9. The preparation method is prepared by any one of claims 1-9.
Citation Information
Patent Citations
A solid nanoparticle with inorganic coating
CN105377244A
Composition of magnetic nano dropping liquid, magnetic contrast agent and preparation method of magnetic contrast agent
CN113694215A